2013
DOI: 10.1093/ejo/cjs095
|View full text |Cite
|
Sign up to set email alerts
|

Insertion torque, pull-out strength and cortical bone thickness in contact with orthodontic mini-implants at different insertion angles

Abstract: This study aimed to evaluate biomechanical behaviour of inclined orthodontic mini-implants by analyzing its insertion torque (IT), axial pull-out strength (APS), and cortical bone thickness in contact with mini-implant (CBTC). A total of 102 mini-implants were inserted at 90 degree, 60 degree, and 45 degree to the surface of synthetic bone. Peak IT was measured, and the mini-implants were aligned with the mechanical testing machine to record the APS. The cortical bone thickness in contact with each mini-implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…An in vitro study, which did not take into consideration different cortical bone thickness, reported that angled insertion provides greater MIT as a consequence of increased contact in the mini-implant-cortical bone interface 37 . The results of this present study suggest that the characteristics of the alveolar cortical bone should be taken into consideration when determining a suitable placement angle for mini-implant insertion.…”
Section: Discussionmentioning
confidence: 69%
“…An in vitro study, which did not take into consideration different cortical bone thickness, reported that angled insertion provides greater MIT as a consequence of increased contact in the mini-implant-cortical bone interface 37 . The results of this present study suggest that the characteristics of the alveolar cortical bone should be taken into consideration when determining a suitable placement angle for mini-implant insertion.…”
Section: Discussionmentioning
confidence: 69%
“…Studies investigating the stability of mini‐implants have focused on measures of mechanical strength, including insertion torque (IT) [1,2], removal torque (RT) [3], and pullout strength [4–6]. The procedures used to analyze these measures are nonrepeated, invasive, and destructive.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies have examined mini‐implant stability, including the insertion torque (IT) [4,5], removal torque [6,7], and vertical and horizontal pullout strength (HPS) [8–10]. Because of immediate loading, the stability of a mini‐implant relies on the mechanical interlocking between the mini‐implant thread and the surrounding bones.…”
Section: Introductionmentioning
confidence: 99%